Spleen Tyrosine Kinase Is a Critical Regulator of Neutrophil Responses to Candida Species - Paige E. Negoro; Shuying Xu; Zeina Dagher; Alex Hopke; Jennifer L. Reedy; Michael B. Feldman; Nida S. Khan; Adam L. Viens; Natalie J. Alexander; Natalie J. Atallah; Allison K. Scherer; Richard A. Dutko; et al. (mBio, 2020)
ABSTRACT Invasive fungal infections constitute a lethal threat, with patient mortality as high as 90%. The incidence of invasive fungal infections is increasing, especially in the setting of patients receiving immunomodulatory agents, chemotherapy, or immunosuppressive medications following solid-organ or bone marrow transplantation. In addition, inhibitors of spleen tyrosine kinase (Syk) have been recently developed for the treatment of patients with refractory autoimmune and hematologic indications. Neutrophils are the initial innate cellular responders to many types of pathogens, including invasive fungi. A central process governing neutrophil recognition of fungi is through lectin binding receptors, many of which rely on Syk for cellular activation. We previously demonstrated that Syk activation is essential for cellular activation, phagosomal maturation, and elimination of phagocytosed fungal pathogens in macrophages. Here, we used combined genetic and chemical inhibitor approaches to evaluate the importance of Syk in the response of neutrophils to Candida species. We took advantage of a Cas9-expressing neutrophil progenitor cell line to generate isogenic wild-type and Syk-deficient neutrophils. Syk-deficient neutrophils are unable to control the human pathogens Candida albicans, Candida glabrata, and Candida auris. Neutrophil responses to Candida species, including the production of reactive oxygen species and of cytokines such as tumor necrosis factor alpha (TNF-α), the formation of neutrophil extracellular traps (NETs), phagocytosis, and neutrophil swarming, appear to be critically dependent on Syk. These results demonstrate an essential role for Syk in neutrophil responses to Candida species and raise concern for increased fungal infections with the development of Syk-modulating therapeutics. IMPORTANCE Neutrophils are recognized to represent significant immune cell mediators for the clearance and elimination of the human-pathogenic fungal pathogen Candida. The sensing of fungi by innate cells is performed, in part, through lectin receptor recognition of cell wall components and downstream cellular activation by signaling components, including spleen tyrosine kinase (Syk). While the essential role of Syk in macrophages and dendritic cells is clear, there remains uncertainty with respect to its contribution in neutrophils. In this study, we demonstrated that Syk is critical for multiple cellular functions in neutrophils responding to major human-pathogenic Candida species. These data not only demonstrate the vital nature of Syk with respect to the control of fungi by neutrophils but also warn of the potential infectious complications arising from the recent clinical development of novel Syk inhibitors for hematologic and autoimmune disorders.